Cross-sectional and descriptive study of centrofacial fractures at the Cocody University Hospital Center from 2016 to 2020: Centrofacial fractures: State of play at Cocody University Hospital - Koffi, Konan Marc; Alexandre De Misères , Ory Opokou; Laurent , Boka Koffi; Lucien Jonathan, Yapo Aké; Lucien , Asseke Assoumou; Béatrice, Harding Mouan; Bakary , Ouattara; Béatrice , Ettien (Journal of Surgery and Medicine, 2023)
Background/Aim: Centrofacial fractures resulting from high-impact violence can be considered mild traumatic brain injuries. Given the complexities and associated risks, a comprehensive examination of these fractures is warranted. These fractures are increasingly prevalent among young adult patients and are commonly associated with road traffic accidents. In the literature, only a few studies have focused on this particular type of facial bone lesion. In Ivory Coast, no studies have been conducted on these fractures, which highlights the importance of our research aimed at describing the epidemiological and anatomical-clinical characteristics of centrofacial fractures in the stomatology and maxillofacial surgery department of the Cocody Teaching Hospital. Methods: This descriptive cross-sectional study was conducted in the Stomatology and Maxillofacial Surgery Department of the Cocody University Hospital Center from January 2016 to December 2020. Results: The prevalence of these fractures was 24.20%, with a predominance of male subjects. The age group most affected was 20 to 40 years old, accounting for 70.96% of cases, and most patients resided in Abidjan (59%). All socio-economic categories were represented, with a higher proportion of individuals in liberal professions (91.4%). Road traffic accidents involving two-wheeled vehicles were the primary cause of these fractures (76.8%), with the most common injury site being the naso-ethmoido-maxillo-fronto-orbital complex (NEMFOC) (32.5%). Conclusion: The epidemiological characteristics of centrofacial fractures associated with two-wheeled vehicles in the Abidjan metropolis of Côte d'Ivoire suggest the need for increased accountability among motor vehicle drivers and stricter enforcement of traffic laws.